Comparison of surgical and non-surgical treatments for 3- and 4-part proximal humerus fractures: A network meta-analysis. (April 2020) - Orman, Sebastian; Mohamadi, Amin; Serino, Joseph; Murphy, Jordan; Hanna, Philip; Weaver, Michael J; Dyer, George; Nazarian, Ara; Keudell, Arvind von
Introduction: Common treatment strategies for proximal humerus fractures include non-surgical treatment, open reduction internal fixation, hemiarthroplasty, and reverse total shoulder arthroplasty. There is currently no consensus regarding the superiority of any one surgical strategy. We used network meta-analysis of randomized controlled trials to determine the most successful treatment for proximal humerus fractures. Methods: MEDLINE, EMBASE, Web of Science, and Cochrane Central electronic databases were searched for randomized controlled trials comparing 3- and 4-part proximal humerus fracture treatments. Data extraction included the mean and standard deviation of clinical outcomes (Constant, DASH), adverse events, and additional surgery rates. Standard Mean Difference was used to compare clinical outcome scores, and pooled risk ratios were used to compare adverse events and additional surgeries. Results: Eight randomized controlled trials were included for network meta-analysis. Non-surgical treatment was associated with a lower rate of additional surgery and adverse events compared to open reduction internal fixation. Reverse total shoulder arthroplasty resulted in fewer adverse events and a better clinical outcome score than hemiarthroplasty. Non-surgical treatment produced similar clinical scores, adverse event rates, and additional surgery rates to hemiarthroplasty and reverse total shoulder arthroplasty. Conclusion: Non-surgical treatment results in fewer complications and additional surgeries compared to open reduction internal fixation. Preliminary data supports reverse total shoulder arthroplasty over hemiarthroplasty, but more evidence is needed to strengthen this conclusion.